A Novel Overlapped Compensation Structure and Its Effectiveness Verification for Expansion Joints in Plate-Type PMEDS Vehicles - Shuqing Zhang; Siyi Wu; Hongfu Shi; Zhengyan Li; Zigang Deng (Actuators)
In the plate-type permanent magnet electrodynamic suspension (PMEDS) vehicle, expansion joints in discrete conductive plates trigger the eddy current truncation effect, thereby causing an attenuation in the levitation force. To address this issue, a novel overlapped compensation structure is proposed, and its effectiveness is verified via simulation and experiment. First, the overlapped compensation structure and principle are introduced, followed by its theoretical model. Additionally, the comparative time-varying levitation force, along with its attenuation percentages, is analyzed under different guideways. Additionally, the optimal structure specifications covering overlapped thickness and length are studied, followed by a design guideline. In addition, dynamic analysis of a single bogie is carried out to analyze the effectiveness of the overlapped compensation structure in terms of vertical stability improvement. Lastly, the equivalent experiments are implemented to further confirm the proposed overlapped compensation structure. The experiment’s result reveals that compared to the original guideway expansion joint, the overlapped compensation structure can reduce levitation force attenuation by 20%. This work is expected to provide a reference for conductive plate guideway establishment in practical applications.